2007
DOI: 10.1149/1.2429042
|View full text |Cite
|
Sign up to set email alerts
|

In Situ AFM Measurements of the Expansion and Contraction of Amorphous Sn-Co-C Films Reacting with Lithium

Abstract: In situ atomic force microscopy measurements of patterned amorphous Sn-Co-C sputtered films reacting with Li in an electrochemical cell have been made. Prismatic-shaped patches of Sn0.34Co0.19normalC0.47 were found to undergo reversible volume expansion of 175±5% [(Vfinal−Vinitial)∕Vinitial] without fracture. The a-Sn0.34Co0.19normalC0.47 was found to have a reversible specific capacity of 700±10mAh∕g when cycled vs a Li metal negative electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 10 publications
2
42
0
Order By: Relevance
“…Using in situ AFM, Lewis et al [39] showed that sputter-deposited films of Sn 0.34 Co 0.19 C 0.47 expand and contract by 175% between the unlithiated and fully lithiated states. This material was measured for four charge-discharge cycles and the volume expansion changed very little between each cycle.…”
Section: Negative Electrodes For Li-ion Batteries 545mentioning
confidence: 99%
“…Using in situ AFM, Lewis et al [39] showed that sputter-deposited films of Sn 0.34 Co 0.19 C 0.47 expand and contract by 175% between the unlithiated and fully lithiated states. This material was measured for four charge-discharge cycles and the volume expansion changed very little between each cycle.…”
Section: Negative Electrodes For Li-ion Batteries 545mentioning
confidence: 99%
“…Sn-based alloys have been intensively studied as negative electrode candidates for Li-ion batteries in the last decade because of their much higher specific and volumetric capacity compared with graphite [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. However, they suffer from large-volume expansion during lithiation, which presents a huge challenge for capacity retention.…”
Section: Introductionmentioning
confidence: 99%
“…The first commercially available amorphous tin-based composite anode was introduced to the market by Sony in 2006 [21], followed by detailed studies of Sn 0.34 Co 0.19 C 0.47 systems by Dahn et al [22], which demonstrated the capabilities of these electrodes in high energy Li-ion systems.…”
Section: Introductionmentioning
confidence: 99%